Estrutura genética em Pristimantis latro (Anura: Craugastoridae) - CORNÉLIO, Gilcilene Santana (2022)
Anuran amphibians are indicated as a group of high cryptic diversity in Tropical regions, due to the strong phenotypic conservatism present among species. The presence of a high genetic structure between populations. The Pristimantis genus is the most diverse among all Vertebrates, with more than 526 species. Pristimantis latro Oliveira, Rodrigues, Kaefer, Pinto and Hernández-Ruz 2017, is distributed in the eastern Amazon, between the Tapajós and Tocantins-Araguaia rivers, occupying two banks of the Xingu River. Not too long ago, P. latro was erroneously identified as P. fenestratu. Due to little knowledge about P. latro, we used the mitochondrial genes 16S and IOC to 1) evaluate patterns of genetic structure; 2) test the relation between the genetic and geographical distance between the locations; 3) reconstruct phylogenetic relationships among populations; and 4) Assess the time of divergence between the sampled locations. Pristimantis latro presented a strong genetic structure among the populations of the left and right banks of the Xingu River of the same margin. Recent rivers may represent recent or semi permeable barriers, as found in amphibians and squamates in the Tapajós River. Through observations, we found a spatial pattern of genetic distribution similar to that proposed as a rivers barrier hypothesis by Wallace (1849). Such pattern has been found in studies with terrestrial Vertebrates. This pattern resembles this in Allobates, anuro of terrestrial reproduction similar to the Pristimantis species. Its life history, river barrier, isolation by distance, and a high diversity of habitats in the Amazon, are some of the factors that were responsible to populate this proclaimed structuring in P. latro.